Strategi Pemasaran Sekolah dalam Menarik Minat Masyarakat - Basorah, Muhamad; Erny Roesminingsih; Amrozi Khamidi (Kelola: Jurnal Manajemen Pendidikan, 2024)
Various strategies, innovations, and expansion activities in different agencies, institutions, or organizations are being intensively implemented to keep pace with the ever-changing times. In this research, observation, interviews, and documentation activities were conducted using qualitative research methods to explore the school marketing strategy through innovation and expansion at SMA Muhammadiyah 1 Gresik. SMA Muhammadiyah 1 Gresik offers four educational programs: boarding school management, virtual classes, cooperation with foreign schools, and international school programs. This research utilized three data collection techniques: interviews, observations, and documentation. The research subjects consisted of three individuals: the Vice Principal of Curriculum, the Vice Principal of Facilities and Infrastructure, and the Vice Principal of Public Relations. Data analysis was conducted in three stages: data reduction, data presentation, and data verification. The results of this study show that marketing strategies are carried out both internally and externally. Adequate facilities and infrastructure are key components of the school marketing strategy. The school also promotes its programs by organizing events related to these initiatives. These efforts have led to an increase in student enrollment at SMA Muhammadiyah 1 Gresik.